1989
DOI: 10.1007/bf00378745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbial floras on the distributions of five domestic Drosophila species across fruit resources

Abstract: The distributions of five Drosophila species and four components of the microflora have been compared across a total of 48 traps baited with four different fruit and vegetable substrates in two domestic compost heaps in Canberra (Australia). Large and consistent differences are found, both among the Drosophila and among the microbial classes, in their distributions across traps baited with different substrates. Moreover the distribution of each Drosophila species shows a unique set of strong associations with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…The pH value of cantaloupe puree agrees with results of Syahidah et al [58], who reported the pH value to range between 6.46 and 6.48. As for Squash puree the results are in agreement with work by Oakeshott, [43] who reported the pH values as weakly basic in zucchini (8.2-8.3) but the pH value of butter is 6.69 which agrees with work by Ozkan et al [45]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The pH value of cantaloupe puree agrees with results of Syahidah et al [58], who reported the pH value to range between 6.46 and 6.48. As for Squash puree the results are in agreement with work by Oakeshott, [43] who reported the pH values as weakly basic in zucchini (8.2-8.3) but the pH value of butter is 6.69 which agrees with work by Ozkan et al [45]. …”
Section: Discussionsupporting
confidence: 91%
“…Texture tends to become softer as the pH increases. The change in pH of batter is due to the addition of cantaloupe puree, which has a pH of 6.46 and squash puree, with a pH of 8.2 [43]. Table (3) presents physical properties of cake with and without fat replacer.…”
Section: Specific Gravity and Ph Of Cakesmentioning
confidence: 99%
“…Even though several comprehensive studies on the yeast species and yeast communities that are associated with drosophilids exist (Dobzhansky et al, 1956;Fogleman et al, 1981;Kearney, 1982;Starmer, 1982a,b;Fogleman & Starmer, 1985;Ganter, 1988;Oakeshott et al, 1989;Morais et al, 1994), surprisingly little is known about the influence of dietary yeast species on the insect's life-history. Among the yeast species shown to be associated with D. melanogaster, the ones chosen in this study, turned out to allow a high survival of larvae until the adult stage.…”
Section: Discussionmentioning
confidence: 99%
“…2). Drosophilid larvae feed on yeast or bacteria on substrates on which their parent lay eggs, and some drosophilids show a preference for specific yeasts or bacteria (Kearney & Shorrocks, 1981;Oakeshott et al, 1989). The growth of some microbes is inhibited by sesquiterpenes produced by certain species of Agaricales (Lactarius vellereus: Sterner et al, 1985).…”
Section: Discussionmentioning
confidence: 99%